2009
DOI: 10.1111/j.1399-0012.2008.00908.x
|View full text |Cite
|
Sign up to set email alerts
|

Focal segmental glomerular sclerosis in renal transplant recipients: predicting early disease recurrence may prolong allograft function

Abstract: Recurrence of focal segmental glomerular sclerosis (FSGS) in the allograft following renal transplantation can be graft threatening. To assess risk factors associated with FSGS recurrence, we analyzed 22 patients with FSGS who underwent transplantation between 1996 and 2004. Five patients (Group I, 23%) developed FSGS post-transplantation. Of these patients, 60% had undergone bilateral nephrectomy (BN) for progressive disease compared with none of the patients that were free of recurrence (Group II) (p = 0.000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
4
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 23 publications
2
54
4
2
Order By: Relevance
“…Three studies report data regarding gender and all found an increased incidence in females. Sener et al [10] found a statistically significant difference with only one male compared to 50 % of females having recurrent FSGS. The gender difference in the other two studies is not as striking, but they still report a 29 and 41 % incidence in males and a 36 and 63 % incidence in females [5,8].…”
Section: Epidemiologymentioning
confidence: 95%
See 2 more Smart Citations
“…Three studies report data regarding gender and all found an increased incidence in females. Sener et al [10] found a statistically significant difference with only one male compared to 50 % of females having recurrent FSGS. The gender difference in the other two studies is not as striking, but they still report a 29 and 41 % incidence in males and a 36 and 63 % incidence in females [5,8].…”
Section: Epidemiologymentioning
confidence: 95%
“…Recurrent FSGS resulted in a loss of the expected living-donor graft survival advantage [16]. In contrast, Sener et al [10] found no adverse effect of recurrent disease on allograft survival in patients with FSGS. A similar finding was also reported by Jungraithmayr in a series of 86 pediatric patients [11].…”
Section: Epidemiologymentioning
confidence: 96%
See 1 more Smart Citation
“…In Schachter's material recurrence rate was 23% of patients with biopsy proven primary FSGS (55). Sener et al have reported that post-transplant recurrence of FSGS may be associated with bilateral nephrectomy indicated in some patients with catastrophic NS (70). These patients should be monitored closely for early recurrence and may benefit from early PP treatment (70).…”
Section: Prognosismentioning
confidence: 99%
“…This may delay diagnosis and treatment which may affect outcome (2). Our program follows a protocol for transplantation of patients with FSGS that includes intensive monitoring for the recurrence of proteinuria after transplantation and plasma exchange in patients suspected of developing recurrent disease.…”
Section: Introductionmentioning
confidence: 99%